The Effectiveness of Investigative Audit Implementation in Detecting Fraud in Review of Independence and Application of Computer-Assisted Audit Techniques - Habiba, Habiba; Pitria, Melani; Syahfitri, Adinda; Rizkina, Miftha (EDUCTUM: Journal Research, 2025)
Investigative audits have become a crucial tool in detecting and proving increasingly complex fraud in both the public and private sectors. This study aims to analyze the influence of auditor independence and the application of Computer-Assisted Audit Techniques (CAA) on the effectiveness of investigative audits. Through a literature review approach, data were collected from various journals and related literature sources. The study results indicate that strong auditor independence and the use of technology through CAA can improve the effectiveness of investigative audits. The combination of these two factors strengthens the auditor's ability to uncover indications of fraud accurately, quickly, and objectively. This research is expected to provide input for auditors and supervisory agencies to optimize investigative audit practices in preventing and addressing fraud.